An overview of the rule of law values within Malaysia's anti-terror law: A legal perspective from India and the United Kingdom - Ho, Peng Kwang (Universiti Utara Malaysia Press, 2017)
Changes in the legislative framework in response to terrorist threats in Malaysia, India and the United Kingdom since the 9/11 attacks have witnessed the integration of national security issues and criminal justice to form part of the extraordinary security laws passed by the authorities. This integration has rested on the premise that terrorism is an unprecedented threat and so it requires legislation tailored to what has been called as a ‘new paradigm in prevention. The criminal law has largely, though not exclusively, focused only on dealing with crimes that have already taken place. However, the reason for the shift in states emphasis towards prevention in counter-terrorism is that terrorism is an extraordinary threat that calls for a special response. A unique theme of most anti-terror legislations is focusing on what is referred to by the government as ‘prevention’ - hoping to foil foreseeable attacks from the terrorists. However, the key concern is the impact on the Rule of Law values when applying the anti-terror laws. This article argues that the preventive methods adopted by Malaysia, India and the United Kingdom are effective in forestalling terrorist activities to a certain extent, but often this comes at a high price to pay when individual human rights are sacrificed along the way.Further, anti-terror legislation has degraded the Rule of Law values in response to terrorism threat or national security.